Proteomic Biomarkers Panel: New Insights in Chronic Kidney Disease. (7th September 2016) - Mihai, Simona; Codrici, Elena; Popescu, Ionela Daniela; Enciu, Ana-Maria; Rusu, Elena; Zilisteanu, Diana; Albulescu, Radu; Anton, Gabriela; Tanase, Cristiana
Abstract : Chronic kidney disease, despite being a "silent epidemic" disease, represents one of the main causes of mortality in general population, along with cardiovascular disease, which is the leading cause of poor prognosis for these patients. The specific objective of our study was to characterize the relationship between the inflammatory status, the bone disorders markers, and kidney failure in chronic kidney disease patient stages 2–4, in order to design a novel biomarker panel that improves early disease diagnosis and therapeutic response, thus being further integrated into clinical applications. A panel of proteomic biomarkers, assessed by xMAP array, which includes mediators of inflammation (IL-6, TNF- α ) and mineral and bone disorder biomarkers (OPG, OPN, OCN, FGF-23, and Fetuin-A), was found to be more relevant than a single biomarker to detect early CKD stages. The association between inflammatory cytokines and bone disorders markers, IL-6, TNF- α, OPN, OPG, and FGF-23, reflects the severity of vascular changes in CKD and predicts disease progression. Proteomic xMAP analyses shed light on a new approach to clinical evaluation for CKD staging and prognosis.